How do you verify the identity sintheta/(1-cottheta)+costheta/(1-tantheta)=sintheta+costheta?

1 Answer
Sep 6, 2016

LHS:

=sintheta/(1 - costheta/sintheta) + costheta/(1 - sintheta/costheta)

=sintheta/((sin theta - costheta)/sintheta) + costheta/((costheta - sin theta)/costheta)

=(sinthetasintheta)/(sin theta - costheta) + (costhetacostheta)/(costheta - sintheta)

=(-sin^2theta + cos^2theta)/(costheta - sin theta)

=(cos^2theta- sin^2theta)/(costheta - sintheta

=((costheta + sin theta)(costheta - sin theta))/(costheta - sin theta)

=((costheta + sin theta)cancel(costheta - sin theta))/cancel(costheta - sin theta)

=costheta + sintheta

LHS = RHS

Hopefully this helps!